Critical Approach to the Process of Energy Efficient Building Constructing - Arfaei, Aref (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
Now days in all over the world; most of statehoods are applying energy efficiency regulations to the process of construction in their own countries beside regulate standards for historical and existing buildings in their borders. It seems necessary to use these codes to have a more sustainable life and help the future of our planet and posterity, to give them a chance for living in better condition. Regulating energy standards started in Scandinavian countries and developed through the technology in Germany and grew to all Europe and America. Faster and faster most countries started to regulate standards according to climatic changes and other factors in their own situation. Due to technological advances and update the knowledge about ways of using energy and a different source of energy efficiency standards for the building construction process, codes and standards started to adapt to new information and situation. Every day the number of countries which they are starting to apply energy regulations in their countries are increasing, but in-between there are some countries that still do not have any codes for energy efficiency, such as the Turkish Republic of Northern Cyprus. This theorem puts the author on to think about the preparing basic information in this field with the hope of having prepared a suitable standard for Northern Cyprus in the future. To reach this aim, many energy efficiency regulations in the building construction process have been studied, analyzed and compared. Similar standards have been found and studied in more detail; finding results of these analyzes are an attempt to find out the best energy method for TRNC. The aim of this research is to see what is the condition of Turkish Republic of Northern Cyprus currently, and what's missing as a background for applying any regulation in different parts of the construction process. This process has been divided into three parts as a design process, construction period and approval process. These divisions have bee done according to the different timing of building construction process to control the amount of energy used in the final product. To be energy efficient it is important to consider energy factors in design part, base of energy efficient design, building will be constructed and at the end level of energy efficiency success should be examined. For each section most suitable regulation is suggested to prepare needed information for regulators to have a clear view of the northern Cyprus case. Keyword: Energy efficiency, building construction process, design regulations, constricting regulations, energy measuring and labeling, and standards development.

ÖZ : İçinde bulunduğumuz günlerde, tüm dünyada; birçok ülke kendi sınırları içerisinde tarihi ve var olan binaların inşası sırasında standart uygulamaların yanı sıra enerji verimliliğini koruyan kurallar uygulamaktadır. Bu kuralları uygulamak gezegenimizin ve gelecek nesillerin daha sürdürülebilir bir yaşam sürdürebilmeleri için gereklilik göstermekle birlikte, onlara daha iyi yaşam koşulları için bir şans sağlayacaktır. Enerji standartları uygulamaları, İskandinav ülkelerinde başlamış, Alman teknolojileri ile gelişmiş ve tüm Avrupa ve Amerika’ya büyüyerek yayılmıştır. Bir çok ülke de iklim değişiklikleri ve kendi durumlarındaki diğer faktörlerden dolayı giderek artarak bu standartları uygulamaya başlamıştır. Bina yapım aşamasında yasa ve standartlar, enerji kullanımı ve farklı enerji verimliliği standartlarının teknolojik avantajlar ve güncel bilgiler sayesinde yenilenmesiyle bu bilgilere ışığında değişmeye başladı. Her gün yeni enerji yasalarını uygulayan ülkeler çoğalmaktadır fakat bununla birlikte halen enerji verimliliği yasalarını uygulamayan ülkeler bulunmaktadır. Kuzey Kıbrıs Türk Cumhuriyeti de bu ülkelerden biridir. Bu tez, yazarı bu konu üzerinde temel bilgileri hazırlamaya itmiş ve Kuzey Kıbrıs'ın geleceğinde kullanılabilir hazır bir standartlar kaynağı hazırlama isteği doğurmuştur. Bu amaca ulaşabilmek için, inşaat aşamasında birçok enerji verimliliği yasası çalışılmış,incelenmiş ve kıyaslanmıştır. Birçok benzer standartlar bulunmuş ve detaylı olarak çalışılmıştır. Bu analizlerin sonuçları KKTC de uygulanabilecek en iyi enerji metodu için bir altyapı oluşturmuştur. Bu araştırmanın amacı, Kuzey Kıbrıs Türk Cumhuriyetinde şu anda içinde bulunulan durumu ortaya koymak ve inşaat aşamalarının farklı noktalarında bu yasaları uygulamak için eksik olan zeminleri saptamaktır. Bu süreç; tasarım aşaması, inşaat aşaması ve onay aşaması olarak üç aşamaya ayrılmıştır. Bu ayrımlar, tamamlanma aşamasına gelininceye kadar izlenen farklı yapım aşamalarındaki enerji kullanımını kontrol edebilmek amacıyla yapılmıştır. Enerji verimliliğini sağlayabilmek için, tasarım aşamasında sürdürülebilir enerji verimliliği göz önünde bulundurularak tasarım yapılması önemlidir. Bina inşasında ve son seviyede de enerji verimliliğinin başarısı incelenmelidir. Kuzey Kıbrıs konusunda net bir görüş ortaya koyabilmek için, her bölüm için en uygun yasalar önerilmiş ve yasalarla ilgili gerekli tüm bilgiler derlenmiştir. Anahtar kelimeler: Enerji verimliliği, binalarda inşaat süreci, tasarım yasaları, kısıtlayıcı yasalar, enerji ölçümü ve sınıflandırma, standart gelişimi
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2014. Supervisor: Assist. Prof. Dr. Polat Hançer.
Keywords: Architecture; Architecture and energy conservation; Buildings - Environmental aspects; Sustainable construction; Sustainable buildings - Economic aspects; and standards development; energy measuring and labeling; Energy efficiency; building construction process; design regulations; constricting regulations